Hubungan Kecerdasan Emosional dengan Kemampuan Bersosialisasi Siswa Kelas Tinggi SDK Ende 3 - Maria Finsensia Ansel; Siti Arafat (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the relationship between emotional intelligence and social skills of students at SDK Ende 3. This study uses a quantitative correlational approach with a population of 335 students in grades IV, V and VI using a purposive sampling technique with a sample determination criterion of 20% of the population, so that the sample obtained amounted to 67 students. Data collection techniques were carried out using emotional intelligence and social skills questionnaires that had been tested for validity and reliability. Data analysis using Pearson product moment correlation technique. The results of the study showed that most students had levels of emotional intelligence and social skills in the moderate category. The results of the correlation test showed an r value of 0.508 with a significance value of 0.000 (p < 0.05), meaning that there is a positive and significant relationship between emotional intelligence and social skills. The conclusion is that emotional intelligence and social skills are interrelated, where the higher the emotional intelligence, the higher the social skills and vice versa, the lower the emotional intelligence, the lower the student's social skills.